Adaptive Leadership in Development course - Moran, Mark; Curth-Bibb, Jodie; Grice, Tim; Glavey, Sarah (University of Queensland, 2017)

AdaptScan - Improving your Team's Adaptive Management - Mercy Corps (Mercy Corps, 2020)

Introduction to Project Management - The Case of GIZ Projects - Lacroix, Eric J. (Khulna University, 2015)
In this course, we will try to understand the complexity and the structure of the management of a development project implemented by the GIZ for the German Development cooperation. We will first define the frame of management and project to enter in the map of two logics. Then, we will overfly the 5 success factors of Capacity WORKS, with concrete examples in annexe. It will bring us to the monitoring, the standard processes in GIZ cooperation projects, the basic tools for project implementation and the evaluation. The team building will allow us to enter in a specific aspect of project management.

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

Si Guides on System Innovation - Colchester, Joss; Si Network (Si Network, 2023)
So you have just hear about systems thinking and systems innovation and are keen to know more, Ok sparky let's get started.We have structured all the content into four main areas that we think you ...

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

UNDP Digital Leadership Learning Modules - UNDP (United Nations Development Programme, 2022)
In order to support the digital transformation of government operations Digital Learning Modules for Civil Servants are available, an off-the-shelf package of capacity development in form of replicable training modules to empower public servants at both the local and central government level to be leaders of digital transformation for delivering better public services. The modules cover a multitude of fundamental areas: comprehending digital government and services, human-centered design for inclusivity and agile learning cycles; feature the importance of security and privacy, the value of data and how to manage data and technology related risks; spotlight the key role of supportive leadership and offer practical tools for assessing and overcoming main barriers to ensure a successful digital transformation journey.

Webinar: Operationalizing Adaptive Management: What it takes. Why it matters. - Mercy Corps (Mercy Corps, 2015)
Development actors increasingly agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. A growing body of evidence supports this claim. But what does adaptive management look like in practice? What does it require of managers and donors to make happen? How can we reconfigure incentives and success metrics to support adaptation, while remaining compliant?